(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article discusses the factors influencing the development of tourism in Uzbekistan. Tourism is a significant source of income, employment, contributes to the diversification of the economy, creating industries that serve this area. In addition, tourism is an essential factor in the implementation of the state’s foreign policy.